Perspectives of Certain Central and Eastern European States Related to International Criminal Law, International Humanitarian Law and International Refugee Law - Rau, Marcin (International Criminal Law, Humanitarian Law and Refugee Law From The Perspective of Human Rights Law, 2026)
This chapter investigates the uneasy relationship between universal international legal norms and the historically shaped realities of Central and Eastern Europe. Through a comparative analysis of selected states, it traces how International Criminal Law, International Humanitarian Law, and International Refugee Law are interpreted, resisted, or adapted in contexts marked by communist legacies, post-conflict transitions, and contemporary geopolitical crises. The discussion moves across three interconnected fields: cooperation with the ICTY in the former Yugoslavia, the legal qualification of communist-era violence in Poland and Hungary, and the divergent responses of Central European states to Ukrainian refugee flows after 2022. Despite formal commitments to international standards and EU frameworks, the chapter shows that legal practice remains deeply contingent on national narratives of victimhood, sovereignty, and historical responsibility. The comparison reveals striking contrasts: from reluctant engagement with war crimes accountability to selective humanitarian openness shaped by cultural proximity. Rather than depicting the region as norm-resistant, the chapter argues that Central and Eastern Europe illustrates a broader truth about international law itself – its effectiveness depends on social legitimacy and contextual resonance. By foregrounding these tensions, the chapter invites a more nuanced understanding of how international law functions beyond textbooks, in societies where law, memory, and politics remain inseparable. Keywords: international law in CEE, transitional justice, war crimes, communist crimes, humanitarian protection, post-communist states, Poland, Hungary, Ukrainian refugees, EU conditionality